Epidemiological situation of congenital anomalies in Paraguay in the period 2017-2021 - Aguilar-Coronel, Sara; del Puerto, Florencia; Fiesco-Roa, Moisés Ó.; Mereles, Juan; Samudio, Margarita (Medicina Clínica y Social, 2025)
Introduction: Congenital anomalies (CA) are structural or functional defects that occur during fetal development and are detected before, during or after birth. They represent an important public health problem due to their contribution to neonatal morbidity and mortality. Objective: To analyze the epidemiological situation of congenital anomalies in Paraguay from 2017-2021, in terms of prevalence and mortality using public data. Methods: Ecological study with data obtained from the digital platform of the Vital Statistics Computer Subsystem (SSIEV) and the Latin American Network of Congenital Malformations (ReLAMC) for the period 2017-2021. Results: Data from 273,239 births were analyzed, cardiac and large vessel anomalies were the most prevalent, accounting for 64% of all CAs. In terms of mortality, 2090 of 2639 deaths occurred in the first 11 months of life. The Central department had the highest frequency of deaths related to CA, with 881 deaths, representing 33.38% of the total. Conclusion: Congenital anomalies, particularly those related to heart defects, represent an important cause of morbidity and mortality in Paraguay. The most affected population was the pediatric population, and a high prevalence of heart and ear defects was observed. These results highlight the need to improve diagnostic and treatment capacities to reduce mortality associated to congenital anomalies.